2014
DOI: 10.1128/jvi.01162-14
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HLA Selection Pressure on HIV Fitness at a Population Level in Mexico and Barbados

Abstract: Previous studies have demonstrated that effective cytotoxic T lymphocyte (CTL) responses drive the selection of escape mutations that reduce viral replication capacity (VRC). Escape mutations, including those with reduced VRC, can be transmitted and accumulate in a population. Here we compared two antiretroviral therapy (ART)-naive HIV clade B-infected cohorts, in Mexico and Barbados, in which the most protective HLA alleles (HLA-B*27/57/58:01/81:01) are differentially expressed, at 8% and 34%, respectively. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 47 publications
1
21
2
Order By: Relevance
“…Certain HLA-associated mutations in Gag have been shown to impair Gag-Protease-mediated viral replication capacity in vitro (Gag-Pro RC). Gag-Pro RC is in turn positively associated with pVL in numerous global cohorts [ 18 , 25 30 ]. In particular, reduced Gag-Pro RC has been observed in predominantly North American cohorts of elite controllers as well as individuals in acute/early infection who express protective alleles B*13, B*27, B*57, and/or B*58:01 [ 18 , 26 ], though the latter associations are less apparent during the chronic phase [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Certain HLA-associated mutations in Gag have been shown to impair Gag-Protease-mediated viral replication capacity in vitro (Gag-Pro RC). Gag-Pro RC is in turn positively associated with pVL in numerous global cohorts [ 18 , 25 30 ]. In particular, reduced Gag-Pro RC has been observed in predominantly North American cohorts of elite controllers as well as individuals in acute/early infection who express protective alleles B*13, B*27, B*57, and/or B*58:01 [ 18 , 26 ], though the latter associations are less apparent during the chronic phase [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study compared Gag-Pro RCs in treatment-naive Mexican and Barbadian HIV-1 subtype B cohorts which differ in their frequency of protective HLA alleles (8 % versus 34 % of B*27/57/58:01/81:01 in Mexico versus Barbados). The study revealed a higher burden of HLA-mediated Gag escape mutations and significantly lower Gag-Pro RC in chronically infected Barbadian compared to Mexican individuals [ 30 ]. Moreover, Gag-Pro RC correlated positively with pVL, supporting the importance of Gag in HIV-1 disease outcome [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation is that the median viral load in our entire cohort was very low making correlations difficult. Nevertheless, multiple prior studies have shown that overall, individuals with protective alleles have lower viral load compared to individuals who lack these HLA-I types 8283848586 . Moreover, this effect can be seen early following viral infection suggesting that CE responses could perhaps be partly responsible for the enhanced viral control afforded to these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Not only does the HLA impact on HIV have an effect on the disease course in any given individual but also it shapes features of the epidemic at the population level. Increased immune pressure in individuals has been reported to reduce the virulence of the virus at a population level (Juarez-Molina et al 2014 ; Payne et al 2014 ; Herbeck et al 2012 ; Kawashima et al 2009 ). However, no clear or substantial decrease in HIV virulence has been observed since the epidemic began; and from the host standpoint, the detrimental effect of viral adaptation to the host HLA type appears greater than the beneficial effect associated with a loss in viral fitness (Carlson et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%